First assessment of debris pollution in the gastrointestinal content of juvenile Magellanic penguins (Spheniscus magellanicus) stranded on the west south Atlantic coasts. (March 2023) - Recabarren-Villalón, Tatiana; Ronda, Ana C.; La Sala, Luciano; Sanhueza, Cristina; Díaz, Lucrecia; Rodríguez Pirani, Lucas S.; Picone, A. Lorena; Romano, Rosana M.; Petracci, Pablo; Arias, Andrés H.
Abstract: This paper provides the first evidence of debris pollution, including plastic, in juvenile Magellanic penguins ( Spheniscus magellanicus ) found stranded on the Atlantic coast of southern Buenos Aires Province, Argentina. Macro-, meso- and microparticles of anthropogenic origin were observed in 100 % of the studied birds, with debris abundance ranging between 33 and 200 items/bird. Microparticles represented 91 % of the total debris and 97 % of them were fibers. Black particles were the most abundant (30 %), followed by transparent (26 %), blue (14 %), yellow (10.3 %), and red (10 %). Infrared and Raman spectroscopy identified 62.7 % of the total particles as plastics, with polypropylene (27.8 %) and polyester (21.6 %) being the most abundant polymers. Semi-synthetic cellulosic fibers, metallic particles, and pigments were also found. The presence of metallic microparticles was suggested for the first time in penguins. Stranded juvenile Magellanic penguins are proposed as promising bioindicators of plastic pollution in the South Atlantic. Graphical abstract: Unlabelled Image Highlights: Magellanic Penguins are vulnerable to marine debris. Urban wastewater and fishing gear may be impacting the penguins foraging areas. Polypropylene and polyester were the most ingested polymers. Magellanic penguins are a promising tool to monitor temporal trends of marine debris.